Nanoenhancer for improving naked DNA electrotransfection In vivo - Wang, Yifei; Wang, Chunxi; Sylvers, Justin; Segura, Tatiana; Yuan, Fan (Frontiers in Bioengineering and Biotechnology, 2023)
Electrotransfection (ET) is a non-viral approach widely used for delivery of naked nucleic acids. Its efficiency can be increased in vitro by treatment of cells with various small molecule enhancers. However, these enhancers often fail to improve ET in vivo, presumably due to rapid clearance in tissues after local injection, reducing their cellular uptake. To this end, we propose to develop a new type of ET enhancers, which we term nanoenhancer, that diffuse slowly in tissues and are poorly absorbed by blood and lymph microvessels. In this proof-of-concept study, we identified two nanoenhancers synthesized with alginate and chitosan and/or poly(ethylene imine) that could be used effectively to improve the efficiency of ET both in vitro and in vivo without compromising cell viability. Mechanisms of the enhancement were related to transient inactivation of nucleases in lysosomes triggered by the nanoenhancer treatment. The concept of nanoenhancer will lead to development of new enhancers that can be used to improve ET efficiency in vivo, highlighting its potential in clinical applications.